Mood symptoms correlate with kynurenine pathway metabolites following sports-related concussion. Issue 6 (12th August 2015) - Singh, Rashmi; Savitz, Jonathan; Teague, T Kent; Polanski, David W; Mayer, Andrew R; Bellgowan, Patrick S F; Meier, Timothy B
Abstract : Objective: An imbalance of neuroactive kynurenine pathway metabolites has been proposed as one mechanism behind the neuropsychiatric sequelae of certain neurological disorders. We hypothesized that concussed football players would have elevated plasma levels of neurotoxic kynurenine metabolites and reduced levels of neuroprotective metabolites relative to healthy football players and that altered kynurenine levels would correlate with post-concussion mood symptoms. Methods: Mood scales and plasma concentrations of kynurenine metabolites were assessed in concussed (N=18; 1.61 days post-injury) and healthy football players (N=18). A subset of football players returned at 1-week (N=14; 9.29 days) and 1-month post-concussion (N=14, 30.93 days). Results: Concussed athletes had significantly elevated levels of quinolinic acid (QUIN) and significantly lower ratios of kynurenic acid (KYNA) to QUIN at all time points compared with healthy athletes (p's<0.05), with no longitudinal evidence of normalization of KYNA or KYNA/QUIN. At 1-day post-injury, concussed athletes with lower levels of the putatively neuroprotective KYNA/QUIN ratio reported significantly worse depressive symptoms (p=0.04), and a trend toward worse anxiety symptoms (p=0.06), while at 1-month higher QUIN levels were associated with worse mood symptoms (p's<0.01). Finally, concussed athletes with worse concussion outcome, defined as number of days until return-to-play, had higher QUIN and lower KYNA/QUIN at 1-month post-injury (p's<0.05). Conclusions: These results converge with existing kynurenine literature on psychiatric patients and provide the first evidence of altered peripheral levels of kynurenine metabolites following sports-related concussion.